The new wave of defensive trade policy measures in the European Union: Design, structure, and trade effects - Fredrik Erixon; Oscar Guinea; Philipp Lamprecht; Vanika Sharma; Renata Zilli Montero (European Centre for International Political Economy (ECIPE), 2022)
This study undertakes a comprehensive review of proposed and adopted defensive trade policy instruments in the EU, with the purpose of better understanding their design, functioning, and implications. The study covers eight policy instruments at different stages of development. These are: Anti-Coercion Instrument (ACI), International Procurement Instrument (IPI), Carbon Border Adjustment Mechanism (CBAM), Foreign Subsidy Instrument (FSI), Corporate Sustainability Due Diligence (DD), Level Playing Field Provisions in the EU-UK Trade and Cooperation Agreement (LPF), Enforcement Regulation (ER), and the Deforestation Initiative (DI).
Keywords: 330; EU foreign trade policy; EU states; EU-Außenwirtschaftspolitik; EU-Staaten